Наукова та педагогічна спадщина професора хімії Івана Красуського в історіографії - Зекунов, Іван Станіславович; Журило, Дмитро Юрійович; Кабачек, Володимир Вікторович (Громадська наукова організація "Всеукраїнська асамблея докторів наук з державного управління", 2023)
Метою статті є відображення біографії професора хімії Івана Адамовича Красуського в науковій літературі. У статті вперше зроблено огляд основних праць, в яких розглянуто найважливіші віхи професійної та політичної діяльності професора хімії Івана Красуського. У статті виконано періодизацію історіографії даного питання, систематизовано основні напрями досліджень радянських і сучасних дослідників, в яких йдеться про відомого викладача та науковця, ім’я якого тривалий час замовчувалося в радянський період. Автори приходять до висновку що аналіз основних етапів професійної діяльності видатних вчених через використання різноманітних джерельних комплексів є перспективним дослідницьким напрямком та дає підстави стверджувати, що в сьогоднішніх умовах, при втраті та недоступності чималої кількості архівних зібрань, є повністю виправданим при відтворенні основних віх професійної діяльності. Дослідження наукового доробку вченого дозволяє окреслити не лише коло його наукових інтересів, але й визначити його співробітників, встановити наукові зв'язки, географію професійної діяльності, оцінити внесок у світову науку.

The purpose of the article is to reflect the biography of Professor of chemistry Ivan Adamovich Krasusky in the scientific literature. For the first time, the article reviews the main works that consider the most important milestones sn the professional and political activitical of chemistry professor Ivan Krasusky. The article periodizes the historiography of this issue, systematizes the main directions of research of Soviet and modern researchers in which we are talking about a well-known teacher and scientist, whose name was hushed up for a long time in the Soviet period. The authors come to the conclusion that the analysis of the main stages of professional activity of outstanding scientists through the use of various source complexes is a promising research direction and gives grounds to assert that in today's conditions, with the loss and unavailability of a considerable number of archival collections, it is fully justified when reproducing the main milestones of professional activity. The study of the scientific heritage of a scientist allows us to outline not only the range of his scientific interests, but also to identify his employees, establish scientific connections, the geography of professional activity, evaluate the contribution to World Science, and outline works in the field of pedagogy. The analysis of the main achievements in the study of this issue proves that the scientific historical literature considered, for the most part, the most important fragments of certain aspects of scientific, political and pedagogical activities of the Professor, some scientists stated his great merits in this field, while others considered Ivan Krasusky exclusively in the political plane -only as a supporter of the old system and the monarchical regime. Nevertheless, V. I. Onoprienko, E. P. Stepanovich, I. M. Shulga, and other modern researchers made a significant contribution to the study of the scientist's life and creative path with their scientific works. Their works became the basis for further research of the scientific and pedagogical achievements of I. A. Krasusky. However, in general, historiography does not fully reveal either his creative path or the scientific and pedagogical heritage left by him.
Scientific and pedagogical heritage of professor of chemistry Ivan Krasusky in historiography
Keywords: хімія; ректор; професор; публікації; статті; Красуський Іван Адамович; chemistry; Rector; Professor; publication; article; Krasusky Ivan